Impact of Islamic built environment criteria on the evolution and architectural character of the urban Hausa traditional house - Babangida, Hamza (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2010)
Extant studies on the Hausa traditional houses dealt more with the physical aspects such as finishing, roofing, decoration and other socio cultural aspects. Although of necessity, there were occasional mentions of the influences of Islam on Hausa traditional architecture in some of these studies. However, these were implicit rather than explicit. This study investigated the impact of Islam on the form and architectural character of the urban Hausa traditional house in northern Nigeria using the kasar Katsina urban traditional house as a case study. Using the non-Muslim rural house as a baseline in the area, the study traces the house evolution in time series since the introduction of Islam. The study identified and explained how the Islamic built environment criteria from the Shari'ah sources were applied in the traditional house building process. Through an extensive field survey, a total of 212 house samples were documented and observed, 120 household heads were administered questionnaires, and 20 key informants were interviewed. Results of the data analysis shows thirty seven generic architectural characters, three Hausa traditional house prototypes based on the frequency occurrences of their architectural characters and six house typologies based on their Islamic criteria response. The quantitative data analysis used as supporting evidence, also shows that the urban Hausa traditional house positively responds to the socio-cultural and environmental needs of the occupants; which is an Islamic housing criteria. Conclusively, therefore, these findings indicated that as in the case of traditional houses in the Arabic –Islamic traditional cities, Islam is the key factor in the evolution, form and the architectural character of the urban Hausa traditional house, relegating climatic conditions, type of building materials and available technology as modifying factors.